EKSPERIMENTASI MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN PAIRS CHECK (PC) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA KELAS VII SMP NEGERI SE-KOTA SURAKARTA - Andini, Fahimah; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This study aimed at determining the effect of models on the learning achievement in Mathematics viewed from the studentsâ logical mathematical intelligence. The learning models compared were learning model of the scientific Team Assisted Individualization (TAI), scientific Pairs Check (PC), and scientific classical. The type of this study was a quasi-experimental study with a 3x3 factorial design. The population was all grade VII students of Junior High Schools in Surakarta. The instruments used for the data collection were mathematics achievement test and logical mathematical intelligence test. The data analysis technique used was unbalanced two ways analysis of variance. Based on the hypothesis, the results of the study can be summarized as follows. (1) The use of Scientific PC resulted better achievement than that of scientific TAI and with scientific classical, the use of scientific TAI resulted better achievement than that of scientific classical. (2) The studentsâ achievement who have high logical mathematical intelligence was better than those who have middle or low logical mathematical intelligence, and students who have middle logical mathematical intelligence were better than those who have low logical mathematic intelligence. (3) At the students with high logical matematical intelligence, scientific TAI, scientific PC, and scientific classical gave the same achievement. At the students with middle logical matematical intelligence, scientific PC gave the better achievement than that with scientific TAI and scientific classical. At the students with low logical matematical intelligence, scientific TAI gave the better achievement than that with scientific PC and scientific classical. (4) In scientific TAI, high logical mathematical intelligence studentsâ achievement was better than the middle one, high and middle level of logical mathematical intelligence studentsâ achievement were better than the lower one. In scientific PC, high logical mathematical intelligence studentsâ achievement have equal achievement to the middle one students, high and middle level of logical mathematical intelligence studentsâ achievement were better than the low one. In scientific classical, high logical mathematical intelligence studentsâ achievement was better than the middle one, high and middle level of logical mathematical intelligence studentsâ achievement were better than the students with low logical mathematical intelligence.Keywords: Scientific TAI, Scientific PC, Scientific Classical, Scientific Approach, Logical Mathematical Intelligence.